FENOMENA HIJRAH SULUKIYAH MAHASISWI MILENIAL PROGRAM STUDI PENDIDIKAN AGAMA ISLAM TAHUN 2016 DI UNIVERSITAS ISLAM MALANG TAHUN 2019-2020 - Binti Uswatul Chasanah; Ahmad Subekti; Moh Muslim (VICRATINA, 2020)
In this study, it was taken from a problem that was found at the time of the study, namely the problem of the hijrah phenomenon that exists among students of the faculties of Islamic Religion, Islamic University of Malang.  Furthermore, this study uses qualitative research methods with the type of case studies, research conducted with several research techniques including interviews.  field observations and documentation.  from the results of the study, researchers found several results, namely: 1) female students in interpreting different migrations and diverse views because they were born from the experience and background of each of them. 2) There are several reasons for them in migrating, such as wanting to live a better life and get closer to Allah and indeed it has become self-awareness to do hijrah.  3) there is an impact in carrying out the hijrah both impacts internally and externally as a whole which has a positive impact  .